Regional Sanctions against Burundi: A Powerful Campaign and Its Unintended Consequences - Julia Grauvogel (German Institute of Global and Area Studies (GIGA), 2014)
This paper examines the impact of regionally imposed sanctions on the trajectory of the Burundian regime and its involvement in the peace process following the 1996 coup in the country. Despite the country's socioeconomic and geopolitical vulnerability, the Buyoya government withstood the pressure from the sanctions. Through a vocal campaign against these sanctions, the new government mitigated the embargo's economic consequences and partially reestablished its international reputation. Paradoxically, this campaign planted the seed for comprehensive political concessions in the long term. While previous literature has attributed the sanctions' success in pressuring the government into negotiations to their economic impact, the government actually responded to the sanction senders' key demand to engage in unconditional, inclusive peace talks under the auspices of the regional mediator once the economy had already started to recover. The regime's anti-sanctions campaign, with its emphasis on the government's willingness to engage in peace talks, backfired, with Buyoya forced to negotiate after having become entrapped in his own rhetoric.
Keywords: 300; sanctions; signals; argumentative self-entrapment; Burundi